DATA PROTECTION LAW AND ITS INTERACTIONS WITH THE ANTI-MONEY LAUNDERING LAW - Garcel,Adriane (2021)
Abstract This article aims to analyze the interactions of the new General Personal Data Protection Law, Law nº. 13,709, of August 14, 2018, with the Money Laundering Law, Law no. 9,613, of March 1998. For this purpose, the methodology used is doctrinal, jurisprudential and quantitative analysis that initially presents the principles expressly established in procedural legislation, and short definitions of their applications. Continuous action addresses the ways in which State courts, already more familiar with this interaction, react and define concepts that are still incipient in national legislation. As a result, it is concluded from the studies presented that the main interaction between the General Law on the Protection of Personal Data (LGPD) and the Money Laundering Law occurs in the institution of a central data monitoring authority at the level national. Having a critical aspect for certain doctrinal aspects, given the right to individual privacy, and as an extremely effective tool, according to divergent opinions, against modern organized crime, which implements, through detailed problems, within the privacy of certain individuals. The main contributions of this study are in the sense of evaluating the interactions that the institution of the National Data Protection Agency (ANPD) and the Money Laundering Law will carry out, especially with regard to the maintenance of a national database, and the implications this brings to the right to privacy and oblivion, in view of the prevalence of the State's interest in combating complex organized crime.